A Critical Analysis of the Green Economy Concept in Mitigating Environmental Impacts - Putra Rizki Julianto; Rohmah Maulidia (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The global economic and financial crisis has shown negative impacts on both humans and the environment. Green growth has become a solution proposed by the OECD to create sustainable development by integrating resource efficiency and environmental impact reduction. In Indonesia, despite rapid economic development, there is often an imbalance with environmental preservation. The concepts of Green Economy and Circular Economy offer more inclusive and sustainable approaches to address these issues. From an Islamic perspective, the principles of Fiqh Al-Bi'ah and maqashid sharia can strengthen the implementation of these concepts to maintain a balance between the economy and the environment. This research uses the library research method by collecting, analyzing, and organizing information from relevant literature such as books, scientific journals, articles, and reports related to sustainability and green economy. The sources obtained were then evaluated for their credibility to delve into the relationship between Green Economy, Circular Economy, and Islamic principles in environmental management, particularly in the rice milling industry. This study found that the implementation of the Green Economy and Circular Economy concepts has the potential to reduce environmental impacts in Indonesia, especially in the rice milling industry. However, the main challenges are inadequate infrastructure and a lack of public awareness. The integration of Islamic principles, such as Fiqh Al-Bi'ah and maqashid sharia, can strengthen the sustainability of green economy implementation by emphasizing the balance between economic growth and environmental preservation.